Amnesty International and Women's Rights Feminist Strategies, Leadership Commitment and Internal Resistances - Ganzfried, Miriam (Edition Politik, 2021)
Amnesty International's (AI) focus on civil and political rights has marked their work with a gender bias from the outset. In the first comprehensive look at AI's work on women's rights, Miriam Ganzfried illustrates the development of their activities regarding women's rights issues over twenty years. Through interviews with staff members and activists and unprecedented access to archive material from the Swiss and the German AI sections, she shows how women activists strategized to make AI increase its work on women's rights. Additionally, the book demonstrates that, despite the leadership's commitment to the Stop Violence Against Women campaign, internal resistance hampered the integration of women's rights into the organization's overall work.